Strategy for Internationalizing Indonesian Higher Education Institutions to Enhance Global Competitiveness - Farida Ayu Brilyanti (Pusbindiklatren Bappenas, 2025)
The global competitiveness of Indonesian higher education institutions (HEIs) remains constrained compared to regional peers. This policy paper examines the root causes, strategic priorities, and actionable reforms needed to accelerate HEI internationalization in Indonesia. Employing a mixed-method approach—combining the 5 Whys technique for qualitative root cause analysis and the Analytic Network Process (ANP) for policy prioritization—this study synthesizes evidence from national focus group discussions, expert interviews, and international benchmarking with Singapore, Malaysia, and China. Findings identify three critical barriers: the absence of an integrated national policy framework, restrictive and fragmented academic visa regulations, and insufficient structural incentives for international research collaboration. Among seven policy options, academic visa reform and mid-term funding for collaborative research emerged as the highest priorities. This study makes a novel contribution by integrating root cause diagnostics with quantitative policy prioritization, offering a structured five-strategy roadmap aligned with Indonesia’s 2025–2045 development vision to strengthen regulatory, institutional, and fiscal foundations for sustainable higher education internationalization